2017
DOI: 10.6061/clinics/2017(04)07
|View full text |Cite
|
Sign up to set email alerts
|

Hepatic Osteodystrophy: The Mechanism of Bone Loss in Hepatocellular Disease and the Effects of Pamidronate Treatment

Abstract: OBJECTIVES:The present study was designed to evaluate the bone phenotypes and mechanisms involved in bone disorders associated with hepatic osteodystrophy. Hepatocellular disease was induced by carbon tetrachloride (CCl4). In addition, the effects of disodium pamidronate on bone tissue were evaluated.METHODS:The study included 4 groups of 15 mice: a) C = mice subjected to vehicle injections; b) C+P = mice subjected to vehicle and pamidronate injections; c) CCl4+V = mice subjected to CCl4 and vehicle injections… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
1
3
0
1
Order By: Relevance
“…Our in viv o and in vitro studies indicate that liver releasing ROS induced expression of Il-17 and Tnfrsf11a in BMCs enhances the osteoclast formation via TNFSF11–TNFRSF11A signaling. Moreover, we show that hepatic ROS-induced osteoblast dysfunction is associated with the bone reduction in CCl 4 -induced mice, as reported previously in cholestasis of patients and bile duct ligated or CCl 4 -treated mice [ 31 , 32 , 40 , 41 ], suggesting that liver releasing ROS exacerbate the bone loss through the imbalance between osteoclast and osteoblast activities in CCl 4 -induced mice. Further functional knock-down of STC1 in donor SHED-Heps attenuate the suppressed osteoclast and inducible osteoblast functions of SHED-HepTx in CCl 4 -induced mice.…”
Section: Discussionsupporting
confidence: 87%
“…Our in viv o and in vitro studies indicate that liver releasing ROS induced expression of Il-17 and Tnfrsf11a in BMCs enhances the osteoclast formation via TNFSF11–TNFRSF11A signaling. Moreover, we show that hepatic ROS-induced osteoblast dysfunction is associated with the bone reduction in CCl 4 -induced mice, as reported previously in cholestasis of patients and bile duct ligated or CCl 4 -treated mice [ 31 , 32 , 40 , 41 ], suggesting that liver releasing ROS exacerbate the bone loss through the imbalance between osteoclast and osteoblast activities in CCl 4 -induced mice. Further functional knock-down of STC1 in donor SHED-Heps attenuate the suppressed osteoclast and inducible osteoblast functions of SHED-HepTx in CCl 4 -induced mice.…”
Section: Discussionsupporting
confidence: 87%
“…HO is an osteometabolic disease that presents with low BMD and changes in bone microarchitecture, and it constitutes a reasonable experimental model for evaluating osteoporosis (46). In this model, hepatic impairment leads to metabolic disturbances that causes loss of bone mass (37,38,46,47), however the pathogenesis is not fully A B understood (48). Some studies have shown that decreased bone formation is the predominant mechanism (47), while others point to increased bone resorption as the main cause of bone loss (49).…”
Section: Discussionmentioning
confidence: 99%
“…This study was conducted using mice femurs obtained from a previous experimental study conducted in our laboratory (37) and approved by the Institutional Animal Care and Use Committee of the Ribeirão Preto Medical School, University of São Paulo (protocol no. 111/2011).…”
Section: Methodsmentioning
confidence: 99%
“…HBV-infected patients exhibited hyperosteoclast function before TAF treatment. Carbon tetrachloride induced liver damage may have increased the levels of TRACP-5b (25), and HOD has been reported to increase TRACP-5b levels in patients with chronic liver disease (6). HOD is based on cirrhosis and is caused by insufficient liver-related factors, vitamin K, vitamin D, parathyroid hormone (PTH) and fibroblast growth factor (FGF)23 (5)(6)(7).…”
Section: Discussionmentioning
confidence: 99%